Catalytic Pyrolysis of Waste Engine Oil over Y Zeolite Synthesized from Natural Clay - Osei, G.K.; Nzihou, A.; Yaya, A.; Minh, D.P.; Onwona‑Agyeman, B. (springer, 2021)
Cheap alumino-silicate materials such as clay materials and Y zeolite were selected for the catalytic pyrolysis of waste engine oil in a fxed bed reactor. A cheaper route of Y zeolite synthesis involving hydrothermal activation of the raw clay and hydrothermal synthesis was employed. X-ray difraction technique, scanning electron microscopy, Fourier transform infra-red, and nitrogen desorption method were used to characterize the intermediate phases formed during the hydrothermal treatment of the clay and the synthesized Y zeolite during the hydrothermal processes. The chemical compositions of the liquid phase of catalytic pyrolysis were characterized by gas chromatography coupled with mass spectroscopy (GC–MS). The results revealed that the alkaline concentration strongly infuenced the activation of the raw clay to obtain a useful phase for the subsequent synthesis of the Y zeolite. The synthesis improved the surface area from 29 m2 /g for the clay to 745 m2 /g for the zeolite. The catalytic pyrolysis resulted in diesel fractions of 64.8 and 54.7%, respectively for the Y zeolite and the clay. It was observed that the gasoline fractions increased to 20.5 and 19.1%, respectively for the zeolite and the clay. In the diesel fraction, the zeolite selectively improved the yield of the cyclo-alkanes which are key constituents in terms of the quality of diesel. Y zeolite was successfully derived from a natural clay and tested in the pyrolysis of waste engine oil. The synthesis route provides the opportunity to improve the catalytic property of the natural clay.
Research Article
Keywords: Waste engine oil; Catalytic pyrolysis; Hydrothermal activation; Y zeolite; Natural clay